Reproduction and feeding habits of the River Catfish Eutropiichthys vacha (Hamilton, 1822) (Siluriformes, Schilbidae) in an impacted habitat: Kotri hydrodam, River Indus, Pakistan - Soomro, Anila Naz; Baloch, Wazir Ali; Jafri, Sayed Iftikhar Hussain; Burdi, Ghulam Hussain; Fulanda, Bernerd (Our Nature, 2013)
Reproduction and feeding habits of Eutropiichthys vacha were studied in Kotri hydrodam, a man-made and human impacted stretch of the Indus River, Pakistan during 2005-2006. A total 303 specimens were sampled and analyzed for maturity stages and gonadal development and food and feeding habits assessed from gut contents. Results showed male dominance over females: sex ratio 1.16:1.0. Minimum size at sexual maturity was 13.9 cm total length (TL). Mean fecundity ranged 1.38x104 to 2.17 x 105. Gonado-somatic index (GSI) was 0.1-2.5 and 0.3-6.5 for males and females, respectively. Highest GSIs were recorded in April. We observe an ontogenic dietary shift in E. vacha: young are omnivorous with insects dominating diet while adults are omni-piscivores with Puntius ticto accounting for 35.4% of species. Other species were Colisa spp., juveniles of Channa spp. and some cyprinids. Feeding intensities were lowest in April at peak of spawning. The intensities increase rapidly after spawning indicating voracious feeding in E. vacha. Feeding intensities in adults are low during the cold season. These results provide for assessment of spatial-temporal variations in feeding intensity in E. vacha while GaSI and diet composition reveal information on environmental shifts and ecosystem fluctuations in the impacted habitats of the River Indus for sound fisheries management. DOI: http://dx.doi.org/10.3126/on.v10i1.7795